ENHANCING VOCATIONAL STUDENTS’ WRITING SKILLS IN PROCEDURE TEXTS THROUGH CANVA APPLICATION: A CLASSROOM ACTION RESEARCH - Trisnani, Eka Suli Suci; Tahrun; Yukamana, Hanni (ELLTER Journal, 2025)
Writing is a creative activity that entails finding and recognizing one's ideas. One definition of writing is the act of turning ideas into words and putting them in writing. This classroom action research aims to overcome students’ problems in writing procedure texts by using the Canva application. There were 17 eleventh-grade students of ATPH at SMKN 1 Tungkal Ilir who enrolled in the academic year 2024/2025 and participated in the study. The researcher used a writing test, observation checklist, and documentation to gather the data. The research was accomplished in three cycles. The criteria of success of this research were 85% of students to get score 75 as the minimum target. In cycle 1, 65% of students got 75. Then, there was an improvement in cycle 2, 76%. Finally, 88% students could achieve score 75 as minimum target in cycle 3. The result of this research indicates that tstudents’ writing skills in procedure text improved after the Canva application was used as the learning tool in the teaching and learning process.